Low inclusion levels of Tenebrio molitor larvae meal in laying Japanese quail (Coturnix japonica, Gould, 1837) diet improve the intestinal morphometry, enzymatic activity and caecal short chain fatty acids profile. (December 2022) - Addeo, Nicola F.; Randazzo, Basilio; Olivotto, Ike; Messina, Maria; Tulli, Francesca; Vozzo, Simone; Attia, Youssef A.; Mahayri, Tiziana M.; Iannaccone, Francesco; Asiry, Khalid A.; Moniello, Giuseppe; Bovera, Fulvia
Abstract: One hundred twenty, 12 weeks old laying Japanese quails (JQ) were equally divided into 4 groups (6 replicates of 5 birds/group). The control group (CON) fed a corn-soybean diet; TML1.4, TML2.8, and TML5.6 groups fed a diet where a Tenebrio molitor larvae meal (TML) was included at 1.4, 2.8, and 5.6%, respectively. The trial lasted 54 days. The villi height (VH) and the crypt depth (CD) linearly decreased from the control to the TML5.6 group ( P < 0.01) in the duodenum, while an opposite trend was observed for the Ab+ mucous cells count ( P < 0.01). The highest VH/CD ratio was found in the TML1.4 group (P < 0.01). In the jejunum a lower VH was observed in the TML1.4 compared to the CON group; the Ab+ mucous cells increased (P < 0.01) according to the increase of the TM inclusion in the diet, while the highest VH/CD ratio (P < 0.01) was recorded in the TML2.8 group. In the duodenum only the L-ANP has been affected by TML ( P < 0.001), with a quadratic and linear effect. The L-ANP is affected by the dietary treatment in the jejunum ( P < 0.05), where showed a quadratic effect with the highest value in TML2.8. The % of butyric acid is maximized (P < 0.05) with the TML1.4 diet and that of the isobutyrate and valeric acids increased (P < 0.01) from TML1.4 to TML5.6. The use of TML at 1.4% in laying quail diets can be considered as a way to improve the intestinal health of the birds. Highlights: Insect meals are studied in poultry nutrition as an alternative protein source or for their effects on intestinal health. Low levels of T. molitor larvae meal in the quail diet improve the intestinal morphometry, enzymatic and microbial activity. The best results were obtained with the lowest inclusion level.